Pengaruh penerapan model project based learning pada mata pelajaran matematika terhadap hasil belajar kelas 5 SDN Kedensari 1 - putri nuzuliah rokhmah; Nurul Aini, S.Pd, M.Pd (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT The low academic achievement of students in geometry topics indicates the need for innovation in instructional methods. This study aims to evaluate the impact of implementing the Project Based Learning (PjBL) model on students' learning outcomes at SDN Kedensari 1. The research employed a quantitative approach with a one-group pretest-posttest design. The research instrument was validated by expert and tested on 30 items, of which only 12 were found to be valid and reliable, with a Cronbach’s Alpha value of 0.858. Pretest and posttest were administered to 17 students as the main data. Normality test results showed that the posttest data were not normally distributed, leading to the use of the Wilcoxon Signed-Rank Test. The analysis revealed a significant improvement between pretest and posttest scores (sig. = 0.00 < 0.05). All students demonstrated academic improvement, with no score decreases observed. The implementation of the PjBL model effectively promoted active student engagement and enhanced conceptual understanding. These findings suggest that PjBL is an effective approach for teaching mathematics at the elementary school level.